Palm Oil and Biodiversity: Mapping the Research Landscape using Bibliometric Methods - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
The rapid expansion of palm oil production has triggered widespread concerns over its impact on global biodiversity, particularly in tropical regions rich in endemic species. This study employs a bibliometric analysis using data exclusively from the Scopus database and visualization through VOSviewer to map the scientific research landscape on palm oil and biodiversity between 2004 and 2024. A total of 980 documents were analyzed to identify key publication trends, influential authors, institutions, countries, and thematic clusters. The findings reveal a significant increase in research output over the past two decades, with a peak in 2019, reflecting growing academic and policy interest in environmental sustainability. Indonesia, Malaysia, and the United Kingdom emerged as the most productive and collaborative countries, while institutions such as IPB University and Universiti Putra Malaysia were identified as central contributors. Keyword co-occurrence and overlay visualizations indicate a thematic shift from ecological impact studies—such as species richness and deforestation—to broader sustainability concerns, including climate change, land use, and conservation policy. The study also highlights research gaps in geographic representation, underexplored taxa, and socio-political dimensions. These insights offer a foundation for guiding future interdisciplinary research and promoting more effective biodiversity conservation strategies in the context of palm oil production.